The Relationship between of Fear of Missing Out (FOMO) on Healthy Jogging Behavior among Adolescents: A Health Belief Model Approach - Diva Rizqi Arifah; Bambang Setiaji; Dian Utama Pratiwi Putri; Atikah Adyas (GLOBAL HEALTH SCIENCE GROUP, 2026)
The rapid expansion of social media use in the digital era has intensified the phenomenon of Fear of Missing Out (FOMO), influencing various aspects of adolescent behavior, including physical activity patterns. Jogging has emerged as a popular and accessible form of exercise among adolescents; however, participation is often driven by social trends rather than sustained health motivation. This study aimed to analyze the influence of Fear of Missing Out (FOMO) on healthy jogging behavior among adolescents in Metro City in 2025 using the Health Belief Model (HBM) framework. A quantitative cross-sectional design was employed involving 100 adolescents aged 15–24 years selected through purposive sampling. Data were collected using validated and reliable questionnaires measuring FOMO and healthy jogging behavior and analyzed using Pearson and Spearman correlation tests. The findings revealed a significant positive relationship between FOMO and healthy jogging behavior (r = 0.252; p = 0.012), as well as between FOMO and weekly jogging frequency (ρ = 0.205; p = 0.041). Duration of social media use was positively associated with both FOMO and jogging behavior, with a strong correlation observed for jogging behavior (ρ = 0.605; p < 0.001). These results indicate that FOMO may function as a digital social trigger that encourages adolescent participation in jogging activities.